2023
DOI: 10.1039/d2np00067a
|View full text |Cite
|
Sign up to set email alerts
|

The scent chemistry of butterflies

Abstract: Butterflies use structurally highly diverse volatile compounds for communication, in addition to visual signals. These compounds originate from plants or a formed de novo especially by male butterflies that possess specific scent organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 239 publications
(618 reference statements)
0
7
0
Order By: Relevance
“…Previous results suggest that most CSG compounds are indeed biosynthesised de novo. [20,48,55] The current analyses and previous work [9,15,20,23] indicate that some compounds or groups are particularly important, in addition to those with proven function (1)(2)(3)(4)(5). These include (E)-β-ocimene (1), (E,E)-α-farnesene and the corresponding epoxidation products, several short alkan-3ones/alk-1-en-3-ones, β-ionone and its dihydro derivative 4, 4hydroxy-isophorone (23), benzyl salicylate (5), [23] as well as several short chain esters (Table 2).…”
Section: Compounds Of the Csgsmentioning
confidence: 80%
See 3 more Smart Citations
“…Previous results suggest that most CSG compounds are indeed biosynthesised de novo. [20,48,55] The current analyses and previous work [9,15,20,23] indicate that some compounds or groups are particularly important, in addition to those with proven function (1)(2)(3)(4)(5). These include (E)-β-ocimene (1), (E,E)-α-farnesene and the corresponding epoxidation products, several short alkan-3ones/alk-1-en-3-ones, β-ionone and its dihydro derivative 4, 4hydroxy-isophorone (23), benzyl salicylate (5), [23] as well as several short chain esters (Table 2).…”
Section: Compounds Of the Csgsmentioning
confidence: 80%
“…The M + ‐ions at m/z 254 for A and 280/282 for B/B’ , indicated that these compounds were butyl, hexenyl and hexyl dodecenoates, respectively, with an uncertain double bond position. The leaf alcohol ( Z )‐3‐hexenol is a common plant constituent formed by lipid degradation, e. g. induced by insect feeding, and has previously been reported in many Heliconius esters [9,19,23] . To determine the double bond position, dimethyl disulfide derivatisation of the CSG extract was performed, yielding a major derivative with a main fragment ion at m/z 173 (SI, Figure S8), indicating a likely double bond at C‐3 of the acid moiety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we incorporated all compounds that were consistently found within a species, including non-pyrrolizidine alkaloid derived compounds. Ithomiini male androconial extracts are dominated by pyrrolizidine alkaloid derivatives, and these are presumed to be the main signalling media (Ehlers & Schulz, 2022; Eisner & Meinwald, 1987; Stefan Schulz et al, 2004). However, recent studies have also found non-pyrrolizidine alkaloid related compounds in the androconial extracts of certain Ithomiini species (Mann et al, 2020; Stamm et al, 2019).…”
Section: Discussionmentioning
confidence: 99%